Understanding The Grievance of Prisoner Toward Imprisonment - Fajar, Udik (Restorative : Journal of Indonesian Probation and Parole System, 2025)
This study investigates the experiences of grief among prisoners related to their incarceration, utilizing Kubler-Ross's five stages of grief—denial, anger, bargaining, depression, and acceptance—augmented by insights from David Kessler. Recognizing grief as a holistic and individualized process impacting physical, mental, social, and spiritual well-being, the research aims to deepen understanding of prisoners' emotional journeys. Conducted with 30 prisoners in Indonesia, the study seeks to inform psychological support strategies and facilitate social reintegration by acknowledging diverse grief responses. The findings underscore the importance of personalized approaches to aid prisoners in progressing toward acceptance and healing within the correctional context